Identification of lysyl oxidase as an adipocyte-secreted mediator that promotes a partial mesenchymal-to-epithelial transition in MDA-MB-231 cells - Cassidy M. Van Stiphout; Grant Kelly; Nikitha K. Pallegar; Eman Elbakry; Ana Valeria Vilchis-Celis; Sherri L. Christian; Alicia M. Viloria-Petit (Open Exploration Publishing Inc., 2024)
Aim: Breast cancer (BC) is the most common cancer in women worldwide, where adiposity has been linked to BC morbidity. In general, obese premenopausal women diagnosed with triple-negative BC (TNBC) tend to have larger tumours with more metastases, particularly to the bone marrow, and worse prognosis. Previous work using a 3-dimensional (3D) co-culture system consisting of TNBC cells, adipocytes and the laminin-rich extracellular matrix (ECM) trademarked as Matrigel, demonstrated that adipocytes and adipocyte-derived conditioned media (CM) caused a partial mesenchymal-to-epithelial transition (MET). Given that MET has been associated with secondary tumour formation, this study sought to identify molecular mediators responsible for this phenotypic change. Methods: Adipocytes were cultured with and without Matrigel, where semi-quantitative proteomics was used to identify proteins whose presence in the CM was induced or enhanced by Matrigel, which were referred to as adipocyte-secreted ECM-induced proteins (AEPs). The AEPs identified were assessed for association with prognosis in published proteomic datasets and prior literature. Of these, 4 were evaluated by the reverse transcription-quantitative polymerase chain reaction (RT-qPCR) and enzyme-linked immunosorbent assay (ELISA), followed by a functional and MET marker analysis of 1 AEP on MDA-MB-231 cells grown on Matrigel or as monolayers. Results: The 4 AEPs showed a positive correlation between protein expression and poor prognosis. RT-qPCR analysis reported no significant change in AEPs mRNA expression. However, lysyl oxidase (LOX) was increased in CM of ECM-exposed adipocytes. Recombinant LOX (rLOX) caused the mesenchymal MDA-MB-231 TNBC cells to form less branched 3D structures and reduced the expression of vimentin. Conclusions: The data suggest that adipocyte-secreted LOX changes the mesenchymal phenotype of BC cells in a manner that could promote secondary tumour formation, particularly at sites high in adipocytes such as the bone marrow. Future efforts should focus on determining whether targeting LOX could reduce BC metastasis in obese individuals.